2015
DOI: 10.1002/chem.201500934
|View full text |Cite
|
Sign up to set email alerts
|

Chemoproteomic Evaluation of the Polyacetylene Callyspongynic Acid

Abstract: Polyacetylenes are a class of alkyne-containing natural products. Although potent bioactivities and thus possible applications as chemical probes have already been reported for some polyacetylenes, insights into the biological activities or molecular mode of action are still rather limited in most cases. To overcome this limitation, we describe the application of the polyacetylene callyspongynic acid in the development of an experimental roadmap for characterizing potential protein targets of alkyne-containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 65 publications
0
20
0
Order By: Relevance
“…[708][709][710] Chemical examination of adult and bud larvae of the chemically-defended sponge Tethya maza indicated that the sterol composition of both were largely similar, suggesting that the larvae are also defended during reproduction. 711 First total syntheses were reported for many compounds including the lipids motualevic acid F, (E)-and (Z)-antazirine, [712][713][714] mycalol (revised to 1105) [715][716][717] and myrmekioside A, 718,719 and polyacetylenes callyspongynic acid, 720,721 phosphoiodyn A and placotylene A. [722][723][724][725] The structure of plakinidone has been corrected to 1106; the compound is highly sensitive to air oxidation.…”
Section: Spongesmentioning
confidence: 99%
“…[708][709][710] Chemical examination of adult and bud larvae of the chemically-defended sponge Tethya maza indicated that the sterol composition of both were largely similar, suggesting that the larvae are also defended during reproduction. 711 First total syntheses were reported for many compounds including the lipids motualevic acid F, (E)-and (Z)-antazirine, [712][713][714] mycalol (revised to 1105) [715][716][717] and myrmekioside A, 718,719 and polyacetylenes callyspongynic acid, 720,721 phosphoiodyn A and placotylene A. [722][723][724][725] The structure of plakinidone has been corrected to 1106; the compound is highly sensitive to air oxidation.…”
Section: Spongesmentioning
confidence: 99%
“…A suite of metabolic enzymes was identified that are involved in the metabolism and degradation of lipids and fatty acids. 9 Here, we prepare the first falcarinol probes capable of bioorthogonal ligation to affinity tags for proteome-wide target identification via quantitative mass spectrometry. [10][11][12] Our studies confirm ALDH2 as a specific target that irreversibly binds to the electrophilic core scaffold of falcarinol via a nucleophilic cysteine.…”
mentioning
confidence: 99%
“…Using conventional synthetic methods to prepare the enantiomers of chiral conjugated diynols has proven challenging . Usually, these diynols are prepared by asymmetric reduction of ynones to form chiral propargyl alcohols, and this is followed by copper‐catalyzed Cadiot–Chodkiewicz cross‐coupling to introduce the second acetylene unit . A shorter pathway requires enantioselective addition of 1,3‐diynes to aldehydes to generate chiral diynols in a single chemical procedure.…”
Section: Introductionmentioning
confidence: 99%